Self-harm as violence: when victim and perpetrator are one (2015)
Violence is standardly defined as behaviour involving physical force intended to hurt, damage or kill. There is no stipulation that the victim and perpetrator cannot be identical. Indeed, The World Report on Violence and Health is explicit that violence can be self-directed as well as other-directed (Krug et al. 2002). Based on this inclusion , it is estimated that 50% of all deaths due to violence are self-inflicted, with 35% due to homicide and the remainder due to war or some other form of conflict (ibid.). Yet, to pick two illustrative examples, not one of the 41 chapters in The Cambridge Handbook of Violent Behaviour and Aggression addresses self-directed violence (Flannery et al. 2007), while the International Handbook of Violence Research devotes only one out of 62 chapters to suicide (Heitmeyer and Hagan 2003). Such collections aim to be far reaching and comprehensive compilations of state-of-the-art research into violence. Why does self-directed violence garner so little attention? One natural answer to this question is that, despite the recognition by the World Health Organization (WHO) that violence can be self-directed, as a society we find it difficult to conceptualize self-harm and suicide as violence at all. One reason for this difficulty may be that our prototype of violence is other-directed. Think of violence, and the kinds of images that immediately spring to mind are likely to include fights, brawls, muggings, gang warfare, military warfare and perhaps sexual violence and the domestic abuse of women and children. But reflection on these images suggests a further reason for this difficulty, namely, that our prototype of the violent perpetrator is male.